Frankenstein's Cat - Curtis Jobling
Be afraid. Be very, very afraid. Because Frankenstein's cat is no ordinary Dr. Frankenstein names his new creation Nine -- not because cats have "nine lives," but because that's how many cats it takes to make him. However, Nine isn't terribly popular at the castle, and he's lonely. So the doctor creates a companion who turns out to be more than Frankenstein's cat bargained for. Curtis Jobling has created a delightful feline hero in Frankenstein's cat. Readers will be laughing out loud at Nine's desire to be normal in a far from normal world.